The Effect of the Massage Method on Labor Pain in the First Active Phase in Maternity Mothers at the Sally Maternity Clinic - Kiki Khoiriyani; Efi Satriana Silalahi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Childbirth is a process of opening and thinning the cervix and uterine contractions occur, causing pain in the delivery process. Labor pain management can be applied non-pharmacologically, one of which is massage that aims to release endorphin compounds so as to reduce pain, reduce anxiety and meaningfully shorten labor time. The purpose of this study is to identify the effect of the massage method on labor pain during the first active phase. The research design used in this study is a quasy-experiment which is two group pretest-postest. The number of samples in this study was 38 people, of which 19 were intervention groups and 19 control groups, with simple random sampling techniques. The data analysis used was t-dependent and t-independent tests. The results of the study obtained the characteristics of the intervention group respondents, most of the respondents aged 24-29 years (42.1%), parity >2 children) as many as 8 people (42.1%), and the level of education was high school as many as 14 people (73.7%). Meanwhile, in the control group, most respondents aged 24-29 years were 7 people (36.8%), parity >2 children were 9 people (47.4%), and high school education level was 18 people (94.7%). The pain intensity in the intervention group before the intervention group averaged 7.26 and after the average was 4.74, while in the control group before the intervention group averaged 7.00 and after the average was 6.16. The results of the t-dependent test of pain intensity before and after the massage in the intervention group were obtained a value of P=0.000 and in the control group before and after the massage was obtained. The results of the independent t-test can be concluded that there is a significant difference after the mass method is carried out in the intervention group, namely the value of P=0.001. From the results of this study, it is known that there is an effect of the massage method on reducing the intensity of labor pain during the first active phase in inpartu mothers. Therefore, it is recommended that midwives apply the massage method as an intervention to reduce pain in the care of normal mothers.